Improving the changes made by the 4th industrial revolution in the industrial management system - Adilov Jafar Zulfali (World Scientific Reports, 2023)
The 4th Industrial Revolution has rapidly transformed numerous aspects of our lives, prompting significant shifts in industrial management systems. As technologies like artificial intelligence, robotics, and the Internet of Things continue to advance, it becomes crucial for businesses to adapt and optimize their management approach to meet the demands of this new era. This essay will delve into the potential improvements that can be made to the industrial management system in the face of the 4th Industrial Revolution.